2016
DOI: 10.1186/s13063-016-1678-5
|View full text |Cite
|
Sign up to set email alerts
|

Glycopyrrolate in comparison to hyoscine hydrobromide and placebo in the treatment of hypersalivation induced by clozapine (GOTHIC1): study protocol for a randomised controlled feasibility study

Abstract: Background: Clozapine is the only medication licensed for the treatment of resistant schizophrenia in the UK. Although efficacious, a common and unpopular side effect of clozapine treatment is clozapine-induced hypersalivation (CIH), which can contribute to non-adherence. The standard treatment for CIH in the UK is hyoscine hydrobromide but this may aggravate cognitive deficits in patients with schizophrenia while glycopyrrolate may be an effective alternative with a more tolerable side effect profile. There i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
2
0
3
Order By: Relevance
“…In addition to atropine, glycopyrrolate is another antimuscarinic administered sublingually, with higher specificity for the M3-M5 muscarinic receptors. It has shown efficacy in multiple disorders of drooling, and researchers have proposed investigation into its efficacy in clozapine-induced sialorrhea [16]. Further approaches might include systemic antimuscarinics, other alphaadrenergic medications, and in serious cases, botulinum toxin injection into the salivary glands [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to atropine, glycopyrrolate is another antimuscarinic administered sublingually, with higher specificity for the M3-M5 muscarinic receptors. It has shown efficacy in multiple disorders of drooling, and researchers have proposed investigation into its efficacy in clozapine-induced sialorrhea [16]. Further approaches might include systemic antimuscarinics, other alphaadrenergic medications, and in serious cases, botulinum toxin injection into the salivary glands [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Die medikamentöse Therapie der Hypersalivation besteht in der Hemmung der Speichelsekretion durch antagonistische Anticholinergika. Im Wesentlichen sind dies Atropin [35][36][37], Scopolamin [38] und Glycopyrrolat (1-8 mg / d) [39][40][41][42][43][44][45][46][47][48], wobei letzteres den Vorteil von allenfalls gering ausgeprägten zentralnervösen Nebenwirkungen hat, eine intakte Blut-Hirn-Schranke vorausgesetzt. Für Kinder und Jugendliche ist seit dem Frühjahr 2018 das Präparat Sialanar ® (320 µg / ml Glycopyrronium) bei schwerer Sialorrhoe regulär rezeptierbar, da es in randomisierten, kontrollierten Studien einen positiven Nutzen bei akzeptablem Nebenwirkungsprofil bei kurzfristiger Anwendung zeigen konnte [49,50]…”
Section: Medikamentöse Behandlungsmaßnahmenunclassified
“…Medical treatment for hypersalivation aims at inhibiting salivary secretion through anticholinergic/antagonistic drugs. Essentially, these are atropine [36][37][38], scopolamine [39], and glycopyrrolate [40][41][42][43][44][45][46][47][48][49]; glycopyrrolate has the advantage of inducing weaker central nervous side effects. For children and adolescents in Germany a formula, Sialanar Ò (320 lg/ml glycopyrronium), became available for prescription since the spring 2018 because randomized controlled studies found a positive effect with a favorable side effect profile [50,51].…”
Section: Medical Interventions Beside Botulinum Neurotoxinmentioning
confidence: 99%